2019
DOI: 10.1007/s12178-019-09546-6
|View full text |Cite
|
Sign up to set email alerts
|

The Hip Labrum Reconstruction: Indications and Outcomes—an Updated Systematic Review

Abstract: Purpose of Review To present an updated systematic review of the indications and outcomes of open and arthroscopic labral reconstruction. Due to the increasing popularity and recognition, the arthroscopic procedure has gained in recent years, the aim was to assess for changes in indications, graft selection, and improvement in outcomes within the last 5 years. Recent Findings A total of nine eligible studies (six case series, one cohort, and two retrospective comparative studies) with a total of 234 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…The results of this systematic review are corroborated by previous reviews, which have demonstrated labral reconstruction to be an effective treatment for irreparable labrum, with good outcomes in properly indicated cases (11,13,23,24). Trivedi et al (11) reported that the score change for mHHS in 10 of 11 studies included in their systematic review ranged from 11 to 36, with the minimal clinically important difference (MCID) being 8 (33,34,41).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The results of this systematic review are corroborated by previous reviews, which have demonstrated labral reconstruction to be an effective treatment for irreparable labrum, with good outcomes in properly indicated cases (11,13,23,24). Trivedi et al (11) reported that the score change for mHHS in 10 of 11 studies included in their systematic review ranged from 11 to 36, with the minimal clinically important difference (MCID) being 8 (33,34,41).…”
Section: Discussionsupporting
confidence: 75%
“…Hip arthroscopy represents the modern and preferred method for labral reconstruction, with arthroscopic procedures constituting 86% of these procedures (24). Arthroscopic procedures result in superior outcomes, lower reoperation rates (25), and expedited recovery compared to surgical dislocation of the hip (26).…”
Section: Introductionmentioning
confidence: 99%
“…In line with my anecdotal experience, hips that undergo labral reconstruction have been shown to have positive outcomes at minimum 2-year follow-up, despite the fact that in many cases, these hips have more damage and a poorer preoperative prognosis, across previously published outcome studies to date [1][2][3] and in this most recent study by Scanaliato et al 5 In this cohort, all hips achieved substantial clinical benefit and exceeded the minimally clinically important difference from preoperatively to postoperatively. Of the 30 hips, 26 (86.7%) returned to play at a median of approximately 6 months.…”
Section: See Related Article On Page 2598supporting
confidence: 78%
“…Use of this procedure has expanded because of innovation in hip arthroscopy techniques and tools; over time, so too has evidence expanded to support this use with high-quality data on patient-reported outcomes. Four review or consensus statements on labral reconstruction outcomes have been published in the past 2 years alone, [1][2][3][4] and outcomes after labral reconstruction have been overwhelmingly positive. The study "Primary and Revision Circumferential Labral Reconstruction for Femoroacetabular Impingement in Athletes: Return to Sport and Technique" by Scanaliato, Chasteen, Polmear, Salfiti, and Wolff 5 in this issue of Arthroscopy provides the next key piece of the puzzle to validating this procedure by reviewing return to sports participation.…”
Section: See Related Article On Page 2598mentioning
confidence: 99%
“…A recent systematic review suggests that current indications for labral reconstruction are young, active patients with no or minimal arthritis (Tönnis 0-1), irreparable or ossified labrum, and hypotrophic <2 mm or dysfunctional hypertrophic labrum >8 mm. 7 The current study by Drager et al 4 now adds evidence for repair in a primary procedure with good quality tissue, even if hypotrophic. Anatomy has to have a place in our hip-preservation approach.…”
Section: See Related Article On Page 2614mentioning
confidence: 62%